(2u+5)(9+u)=0

Simple and best practice solution for (2u+5)(9+u)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2u+5)(9+u)=0 equation:


Simplifying
(2u + 5)(9 + u) = 0

Reorder the terms:
(5 + 2u)(9 + u) = 0

Multiply (5 + 2u) * (9 + u)
(5(9 + u) + 2u * (9 + u)) = 0
((9 * 5 + u * 5) + 2u * (9 + u)) = 0
((45 + 5u) + 2u * (9 + u)) = 0
(45 + 5u + (9 * 2u + u * 2u)) = 0
(45 + 5u + (18u + 2u2)) = 0

Combine like terms: 5u + 18u = 23u
(45 + 23u + 2u2) = 0

Solving
45 + 23u + 2u2 = 0

Solving for variable 'u'.

Factor a trinomial.
(9 + u)(5 + 2u) = 0

Subproblem 1

Set the factor '(9 + u)' equal to zero and attempt to solve: Simplifying 9 + u = 0 Solving 9 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + u = 0 + -9 Combine like terms: 9 + -9 = 0 0 + u = 0 + -9 u = 0 + -9 Combine like terms: 0 + -9 = -9 u = -9 Simplifying u = -9

Subproblem 2

Set the factor '(5 + 2u)' equal to zero and attempt to solve: Simplifying 5 + 2u = 0 Solving 5 + 2u = 0 Move all terms containing u to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2u = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2u = 0 + -5 2u = 0 + -5 Combine like terms: 0 + -5 = -5 2u = -5 Divide each side by '2'. u = -2.5 Simplifying u = -2.5

Solution

u = {-9, -2.5}

See similar equations:

| 4k-12=28 | | h=2+23t-16t^2 | | =9p | | 6-4r=3r-21 | | 180-x=3(90-x)+20 | | 5p+16p+24+6= | | 5x-11y=4 | | 6a^3=12a-5a-10 | | -6+2.4n=2.3-n | | 5x+2-2x+5= | | 8+5f=-12 | | x^2+9x+15=15 | | 7X+3X=8+X+20-1 | | 4x^2+66x-240=0 | | 1-p=-1 | | x=-25+5y | | 3x+1=15+5x | | 5x+.50y=190 | | q^2-10q-20=0 | | x^2+y^2+2x+10y-10=0 | | -(3xy-9)+3(4xy+6)= | | 33+Y=X | | 3(x-7)=23 | | 2n^3+4n^2-7=-8n-2 | | 150*t=16.1t^2+150 | | 1400x=800 | | .75(x+250)=300 | | ((2*x^3*y)-(2*y^3))dy=(3*x^5+3*x^2*y^2)dx | | X+(.15*x)=.79 | | t=16.1t^2 | | -6+2x=-5+x-3 | | 6x+36=48 |

Equations solver categories